Laryngeal function-preserving operation for T4a laryngeal cancer with vocal cord paralysis — A case report. Issue 1 (February 2018) - Asada, Yukinori; Kurosawa, Koreyuki; Matsumoto, Ko; Goto, Takahiro; Katoh, Kengo; Imai, Takayuki; Saijo, Shigeru; Matsuura, Kazuto
Abstract: For locally advanced laryngeal cancers, the standard treatment of choice is chemoradiotherapy if organ function needs to be conserved. Surgical treatment with larynx preservation is conducted only for limited cases. For locally advanced laryngeal cancers such as those with vocal cord fixation and/or cricoid cartilage destruction, there is no apparent standardized organ-preserving surgery keeping the essential laryngeal functions, viz. the airway, deglutition and articulation, uncompromized. Recently, our surgical team saw a patient with T4a advanced laryngeal cancer with vocal cord fixation who aspired to maintain his laryngeal function. Driven by his eagerness, we contrived novel techniques for laryngeal function preservation and performed a two-staged operation. In the first stage, extended vertical partial laryngectomy was conducted including resection of the affected thyroid, arytenoid, and cricoid cartilages, followed by local closure of the hypopharynx. Additionally, laryngeal suspension surgery and cricopharyngeal myotomy were performed in addition to suturing the epiglottis with the intact arytenoid cartilage to enhance swallowing function. In the second stage, airway reconstruction was performed using a local skin flap. As of 10 months after operation, there has been no tumor recurrence, and the reconstructed larynx has been working satisfactorily. In this report we describe an innovative operation that was especially contrived for laryngeal function preservation.